Ljusets betydelse för rotknoppars groningsvillighet i åkermolke (Sonchus arvensis L.) - Åhman, Magnus (2011)
This study is about how changed light conditions induce dormancy in plants. It is divided in two parts. First a literature study where quantification of light, the concept dormancy, photoperiod and light quality are discussed. Second an experimental part, where the importance of light for sprouting capacity in root buds of perennial sow thistle (Sonchus arvensis L.) is investigated. In the science in how flowering in plants are induced the concepts short day/long day plants and light dominant/dark dominant are well-established. These concepts can also be applied to how light induce dormancy in plants. Plants are divided into short-day plants and long-day plants depending on if endodormancy is induced when day length is longer than a critical threshold value (long-day plants) or shorter than a critical threshold value (short-day plants). Plants can detect both light quality and photon irradiance. Both decrease in the dusk and can therefore be of importance to denote the day length. For the most of the plants that has been studied, it has been showed that it is the duration of night length (dark dominant) that is important not the daylight as the classification (short-day/long-day) might trick you to believe. But it also exist plants that the duration of the light is important (light dominant), even then they is less common. Studies in spruce (Picea abies) have showed that light quality might be important for how dormancy is induced. So it is many aspects of lights that theoretically can be of importance for how dormancy is induced in plants. Earlier studies have shown that perennial sow thistle has a dormancy stage in autumn. This reduces the sprouting capacity after fragmentation and makes the plant less vulnerable to mechanical control at autumn. In the experimental part perennial sow thistle was exposed to three treatments: (i) long-day with low intensity (18/6 light/dark, photon irradiance 324 μmol/m2s), (ii) short-day with low intensity (12/12 h light/dark, photon irradiance 324 μmol/m2s) and (iii) short-day with high intensity (12/12 h light/dark, photon irradiance 485 μmol/m2s). Sprouting capacity was evaluated based on proportion of sprouting buds from short fragments. Neither of the daylength treatments used here had any significant effect on sprouting capacity. Sprouting capacity was higher when the irradiance was low. This was not expected and is probably not the cause of dormancy induction in perennial sow thistle.